Le Operette morali e le risorse del dialogo - Caesar, Michael (Rivista Internazionale di Studi Leopardiani, 2023)
The essay analyses the Operette morali with reference to the categories of monologism and dialogism with reference to the two bakhtinian categories of monologism and dialogism. Starting from the assumption that Leopardi is perceived by his readers as a monologic author – one whose voice, even in its variations, remains clearly ascribable to the author himself – Caesar makes this perception interact with the effects of the dominant dialogic form of the Operette, and with the models that shaped the history of this literary genre. By carefully categorizing the interlocutors of Leopardi’s dialogues, he shows how the most famous monologue of the Operette, the one in which Leopardi’s alter ego Filippo Ottonieri takes the stage, powerfully delineates the dialogical dimension of an open thinker and writer.